Shallow and deep foundations in geotechnical engineering - Torrijo Echarri, Francisco Javier (Académica., 2019)
The loads on structures and infrastructures as well as their self-weight are as a set of forces that need to be always transmitted to the ground.This is achieved by means of a foundation,a system composed of a structural transitional element and the support ground, being the latter the component which frequently controls the foundation behavior.This Book includes a series of recommendations and concepts that can be useful in the phase of finding for a suitable foundation solution, in their pre-design phase and in the own foundation design.The final selection of a foundation and its design will require the use of the analytical and/or empirical methods discussed in this text, dedicated to estimate the bearing capacity and the potential settlements of foundations.Thanks to this, the Reader will have the necessary tools for his work as a Civil Engineer specialized in shallow and deep foundations. The Book gathers the different proposal of the main Spanish codes: "Código Técnico de la Edificación","Guía de Cimentaciones en Obras de Carretera" and ROM 0.5.Other bibliography is also included which allow expanding the knowledge discussed here.